Retinal and Choroidal Changes of Vitreoretinal Lymphoma from Active to Remission Phase after Intravitreal Rituximab. (18th May 2020) - Cicinelli, Maria Vittoria; Marchese, Alessandro; Miserocchi, Elisabetta; Giuffré, Chiara; Berchicci, Luigi; Querques, Giuseppe; Bandello, Francesco; Modorati, Giulio Maria
ABSTRACT: Purpose : To identify main qualitative and quantitative changes by spectral-domain optical coherence tomography (SD-OCT) in eyes with vitreoretinal lymphoma (VRL) shifting form active to remission phase, after intravitreal rituximab (IVR). Methods : SD-OCT scans retrospectively assessed for: hyperreflective retinal dots (HRD), intraretinal infiltration, subretinal infiltration, outer retina (OR) fuzzy borders, and pigment epithelium detachments (PED).Central macular thickness (CMT) and choroidal thickness (CT) were measured. These features were examined in active and in remission phase. Results : Eighteen eyes of nine patients enrolled. Patients received 5.3 ± 2.1 IVR according to a 2-weekly or monthly schedule. In remission phase, presence of HRD ( p = 0.02), intraretinal infiltration ( p = 0.02), OR fuzzy borders ( p = 0.01) significantly reduced. Treatment frequency did not influence rate of disappearance of these features. CMT ( p = 0.04) and CT ( P = 0.004) became thinner. Conclusions : Signs referable to lymphoma-induced inflammation (CMT, CT, HRD) and infiltration (intraretinal infiltrates, OR fuzzy borders) decreased in remission phase. Further comparative studies needed to identify the specific role of IVR in inducing these changes.